TPACK-Based Learning Implementation Through Basic Science Books To Enhance Third-Grade Students' Learning Outcomes at SDN 16 Banda Aceh - Filina, Nurul Zikri; Norhazaruddin, Nurul Fatehah Binti; Sahrapi, Peteri Telpi; Fitriansyah, Ota; Fitri, Aida; Nurlina, Nurlina (Jurnal Ilmiah Teunuleh, 2023)
This research aims to determine the improvement in learning outcomes for class III students by implementing TPACK-based learning using basic science books. The research method used in this research is PTK (Classroom Action Research), this research was carried out in 2 cycles with a total of 33 students. Each cycle consists of action planning, observation, and reflection. The data collection technique uses tests, the data analysis technique used uses quantitative descriptive. Increasing student learning outcomes through TPACK-based learning has a positive impact or impact, which is shown by an increase from pre-cycle, cycle I to cycle II. Completeness of student learning outcomes in the pre-cycle was 30% or 10 students out of 33 students, cycle I was 51% or 17 students out of 33 students, cycle II was 91% or 30 students out of 33 students.